Utilization of durian peels (Durio zibethinus) and lubricant treatment sludge as raw materials of Refuse-Derived Fuel - Riza Hudayarizka; Umi Sholikah; Dini Tri Budiarti (Sustinere: Journal of Environment and Sustainability, 2024)
Fossil energy is among the most widely utilized energy sources in Indonesian industry, but its continuous use is leading to its depleted. Refuse-derived fuel (RDF) offers an alternative made from organic and inorganic waste. Durian peel is identified as a promising raw material for RDF due to its high calorific value of 6,274 Kcal/kg. Additionally, Lubricant Treatment Sludge (LTS), which is collected from the oil treatment industry, is used to enhance RDF’s calorific value, as it contains residual oil rich in hydrocarbons. To bind the RDF components, tapioca starch, durian seeds, and rejected papaya were selected as adhesives. The mixture ratios of durian skin, LTS, and adhesive were tested at compositions (90:0:10), (85:5:10), (80:10:10), (75:15:10), and (70:20:10). Subsequent RDF characteristics analyses included tests for moisture content, ash content, volatile matter, fixed carbon, and calorific value. Based on these evaluations, the most optimal composition was determined to be 90% durian peel, 0% LTS, and 10% tapioca starch adhesive. This composition exhibited a moisture content of 1.6%, volatile matter of 74.6%, ash content of 8.4%, fixed carbon of 15.2%, and a calorific value of 3,516 Kcal/kg. Tapioca starch emerged as preferred adhesive due to its favorable properties and characteristics.